Development and Formative Evaluation of a Flipbook-Based Digital Module for Basic Guidance and Counseling - M Fauzi Hasibuan; Sri Ngayomi Yudha Wastuti; Asbi Asbi (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2026)
Digital teaching materials may provide greater visual support, flexibility, and instructional guidance than conventional materials in counselor education. This study aimed to develop a flipbook-based digital teaching module for the Basic Guidance and Counseling course and obtain preliminary evidence of its content feasibility, instructional appropriateness, and lecturer-perceived usability. The study used an ADDIE-informed development research design comprising analysis, design, development, limited implementation, and formative evaluation. The module included learning outcomes, concept maps, instructional content, summaries, assignments, multimedia-supported explanations, navigation features, and references. Formative evaluation involved three guidance and counseling experts and three lecturers. Data were collected using an expert validation sheet, lecturer usability questionnaire, open-ended questionnaire, and focus group discussion guide. Quantitative ratings were analyzed descriptively using a five-point scale, while qualitative comments were categorized and used to revise the module. The mean expert rating was 3.82, indicating that the module was considered feasible according to the predetermined assessment criteria. Lecturer ratings were 3.72 during individual review and 4.14 during limited usability evaluation, while the structured rating obtained following the focus group discussion was 4.66. Feedback resulted in revisions to the module’s language, illustrations, navigation, and implementation guidance. These findings provide preliminary evidence that the module is feasible in content and instructional organization and is perceived by lecturers as usable for Basic Guidance and Counseling instruction. Further evaluation involving students and classroom implementation is required to assess student usability and learning outcomes.